The Employment of ATR-FTIR Spectroscopy for Quantification of Turpentine in Cajuput Oil - Klarisa Sabila; Mazaya Amajida; Hisbullah Hisbullah; Syaifullah Muhammad; Hesti Meilina (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2025)
Cajuput oil is widely used for its therapeutic properties; however, its high economic value makes it vulnerable to adulteration with cheaper solvents, such as turpentine. This study employed ATR-FTIR spectroscopy combined with chemometric methods to qualitatively classify and quantitatively predict turpentine adulteration in cajuput oil. Cajuput oil samples were adulterated with turpentine at concentrations ranging from 0% to 10% (v/v) in 0.5% increments and analyzed in the mid-infrared region (4000–400 cm−1). Spectral pretreatments, including multiplicative scatter correction (MSC), smoothing, baseline correction, second derivative, and standard normal variate (SNV), were applied prior to chemometrics analysis. FTIR spectra revealed the appearance of C=C stretching bands at 1647 and 1508 cm−1 only in the adulterated samples. In contrast, Principal Component Analysis (PCA) with SNV and MSC pretreatments provided clear clustering of samples according to turpentine concentration, with cumulative variances reaching up to 90%. Partial Least Squares (PLS) using MSC, smoothing, baseline correction, and SNV pretreatments yielded excellent calibration and cross-validation performance, with R2 values of 0.98–0.99, and low SEC/SECV and RMSEC/RMSECV values. These results demonstrate that ATR-FTIR spectroscopy combined with appropriate chemometric pretreatments offers a rapid, solvent-free, and reliable approach for authentication and quality control of cajuput oil adulterated with turpentine.